Conductive compositions of conductive polymer and metal-coated fiber

By using a composite of conductive polymer and metal-coated fibers in aircraft composite materials and combining them with polymer matrix, the composite materials' shortcomings in lightning strikes and electromagnetic interference are solved, and the effects of weight reduction and performance improvement are achieved.

JP2025037886APending Publication Date: 2025-03-18THE BOEING CO
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024199424
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2018-06-20
Filing Date
2024-11-15
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The composite components of existing aircraft have shortcomings in resisting lightning strikes and external electromagnetic interference, while the added protective materials will increase weight and increase manufacturing costs.

Method used

New composite materials containing conductive polymers and metal-coated fibers are used, which are contacted with oxidants and monomers to form a composite of conductive polymers and metal-coated fibers and bond them to the polymer matrix.

Benefits of technology

It realizes that while maintaining or improving electrical properties, the weight of composite materials is reduced, the overall weight of the aircraft is reduced, and its protection against lightning strikes and electromagnetic interference is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025037886000008
    Figure 2025037886000008
  • Figure 2025037886000009
    Figure 2025037886000009
  • Figure 2025037886000010
    Figure 2025037886000010
Patent Text Reader

Abstract

To provide compositions containing coated fiber, and vehicle components in which the compositions are arranged.SOLUTION: A composition comprises a conductive polymer, a nickel-coated carbon fiber material, and a polymer matrix or resin, where the conductive polymer is selected from polyaniline (PANI), poly(ethylenedioxythiophene) (PEDOT) or a mixture thereof, and the polymer matrix or resin is polyurethane.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Aspects of the present disclosure provide a composition containing coated fibers, a metal substrate having the composition disposed thereon, a vehicle component having a metal substrate, and a method for producing a metal-coated fiber material having an electrically conductive polymer disposed thereon. [Background technology]

[0002] Vehicles, such as aerospace vehicles, are being designed and built with ever-increasing composite percentages. Composites may be used in a variety of primary and secondary structural structures, for example in aerospace applications, such as composite panels forming the airframe and / or skin (e.g., fuselage, wings, etc.) of an aircraft. The use of composites can provide increased strength and extended service life for various components of aerospace vehicles.

[0003] For aerospace vehicles having composite components (e.g., skin panels), it may be desirable to apply additional materials for lightning strike protection and / or to further reduce external electromagnetic interference (if present) associated with the vehicle's avionics and electronics. Nevertheless, such additional materials undesirably increase the vehicle's weight and increase manufacturing time and costs. Furthermore, forming highly conductive composite components requires a large amount of conductive material as part of the composite component.

[0004] To further improve the overall strength and ductility of composite components, there is a need for composites having electrically conductive materials with reduced weight while maintaining or improving the electrical properties of the composite. There is also a need for methods of making electrically conductive composites and components in which electrically conductive composites are disposed. Summary of the Invention

[0005] The present disclosure provides a composition that includes a conductive polymer and a fibrous material having one or more metals disposed thereon.

[0006] In another aspect, a component comprises the composition of the present disclosure thereon. The component can include a metal.

[0007] In another aspect, a method of making a component includes contacting a metal-coated fiber material with an oxidizing agent and a monomer to form a first composition containing the metal-coated fiber material and a conductive polymer, and contacting the first composition with a polymer matrix or resin to form a second composition.

[0008] In order that the above features of the present disclosure briefly summarized above may be understood in detail in the description of the more particular disclosure, reference will now be made to certain embodiments, some of which are illustrated in the accompanying drawings. However, the accompanying drawings are merely illustrative of typical embodiments of the present disclosure and should not be considered as limiting the scope of the present disclosure, since other equally effective embodiments are also claimed. [Brief description of the drawings]

[0009] [Figure 1] 1 is an aircraft comprising a vehicle component according to one embodiment. [Diagram 2] FIG. 1 is a flow diagram of a method for producing a component having a composition of the present disclosure disposed thereon, according to one embodiment. [Diagram 3] FIG. 2 is a flow diagram of a method for coating a metal-coated fiber with a conductive polymer by template polymerization, according to one embodiment. [Figure 4] FIG. 1 is a flow diagram of a method for producing a component having a composition of the present disclosure disposed thereon, according to one embodiment. [Diagram 5] According to one embodiment, a Fourier transform infrared (FTIR) spectrum shows an overlay of the spectrum of PEDOT-NiCF and the spectrum of NiCF. [Figure 6A] 1 shows a raw energy dispersive X-ray spectroscopy (EDS) spectrum of NiCF according to one embodiment. [Figure 6B] 1 is an EDS spectrum of NiCF—Fe-PTSA according to one embodiment. [Figure 6C] 1 is an EDS spectrum of PEDOT-NiCF according to one embodiment. [Figure 7] According to one embodiment, statistical analysis readout of the examples of the present disclosure.

[0010] To facilitate understanding, the same reference numbers have been used wherever possible to indicate identical elements that are common among the figures, and it is contemplated that elements and features of one embodiment may be beneficially incorporated in other embodiments without further recitation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Aspects of the present disclosure provide a method for producing a coated fiber, a metal substrate having a composition disposed thereon, a vehicle component having a metal substrate, and a metal-coated fiber material having an electrically conductive polymer disposed thereon. The composition includes a conductive polymer and a metal-coated fiber. For example, the composition can include a contact product of a conductive polymer and a metal-coated fiber. In at least one embodiment, a conductive polymer is disposed on the metal-coated fiber. The composition can further include a polymer matrix or a resin. As used herein, a "composition" includes a mixture of components, one or more reaction products, and / or one or more contact products of components. The present disclosure further provides a metal substrate having a composition of the present disclosure disposed thereon. As used herein, a metal substrate includes a pure metal substrate and a metal-containing substrate. The method for producing the composition of the present disclosure includes contacting (e.g., coating) a metal-coated fiber with a conductive polymer or one or more monomers to form a conductive polymer. The method can further include oxidizing the surface of the metal-coated fiber with an oxidizing agent before contacting the metal-coated fiber with the conductive polymer or monomer. The compositions and methods of the present disclosure provide conductive materials, such as conductive composites, with improved electrical properties. For example, the compositions of the present disclosure, including conductive polymers, metal-coated fibers, and polymer matrices or resins, can be used as conductive composite sheets in vehicles. The amount of conductive composite sheets can be significantly reduced compared to conventional composite sheets, resulting in weight savings for the vehicle. Weight savings can result in reduced stiffness and brittleness compared to conventional composite sheets.

[0012] composition The composition of the present disclosure contains a conductive polymer and a metal coated fiber. The composition can further contain a polymer matrix or resin.

[0013] In at least one embodiment, the conductive polymer is selected from polyaniline (PANI), poly(ethylenedioxythiophene) (PEDOT), polypyrrole, polyfluorene, polyphenylene, polypyrene, polyazulene, polynaphthalene, polyacetylene (PAC), poly(p-phenylvinylene) (PPV), polycarbazole, polyindole, polyazepine, polythiophene, or mixtures thereof. The conductive polymer of the present disclosure can provide conductance for static dissipation and / or for surface protection from lightning strikes. For example, the conductive polymer of the present disclosure can provide electromagnetic interference (EMI) shielding, radiation shielding, ionizing radiation shielding, protection from lightning strikes, protection from the environment, insulation from the environment, scratch resistance, etc., to the surface on which the composition of the present disclosure is placed. In at least one embodiment, the composition contains a loading of conductive polymer and metal coated fiber of about 1% to about 30% by weight, e.g., about 1% to about 20% by weight, e.g., 5% to about 15% by weight, based on the total weight of the composition. The loadings of conductive polymer and metal coated fiber in the disclosed percentages improve the overall strength and ductility of the composite components compared to compositions without metal coated fibers, while maintaining or improving the electrical properties of the composite. Additionally, the loadings of conductive polymer and metal coated fiber in the disclosed percentages reduce the overall weight of the composite compared to composites of the same (or similar) conductivity but without metal coated fibers. The ratio of conductive polymer to metal coated fiber is about 0.002:1 to about 4:1, e.g., about 0.004:1 to about 4:1, e.g., about 0.002:1 to about 2:1. Additionally, the metal coated fibers can have an aspect ratio (length divided by diameter) of from about 10 to about 100, such as from about 50 to about 100. Higher aspect ratios result in lower % fill values ​​while maintaining or improving electrical properties.

[0014] The metal-coated fibers according to the present disclosure include neutral metal-coated fibers and oxidized metal-coated fibers. The metal of the metal-coated fibers includes any metal suitable for contacting with a conductive polymer. The metal can be an elemental metal, such as a neutral or oxidized elemental metal, and / or an alloy thereof. In at least one embodiment, the metal is selected from nickel, titanium, palladium, iron, cobalt, copper, aluminum, and chromium. The metal of the present disclosure can provide conductance for static dissipation and / or for surface protection from lightning strikes in addition to the conductive polymer of the present disclosure. For example, the metal of the present disclosure can provide electromagnetic interference (EMI) shielding, radiation shielding, ionizing radiation shielding, protection from lightning strikes, protection from the surrounding environment, insulation from the surrounding environment, scratch resistance, etc. to the surface on which the composition of the present disclosure is placed. In at least one embodiment, the metal coated fiber contains from about 15% to about 70% by weight, such as from about 15% to about 30% by weight, of the metal coating based on the total weight of the metal coated fiber.

[0015] Fibers can provide added strength to a composite and can include carbon (e.g., carbon fibers, such as general-purpose HexForce® carbon fibers from Hexcel® Corporation or TORAYCA® carbon fibers from Toray Industries, Inc.), metallized polymers (e.g., metallized polymer fibers), nylon (e.g., nylon fibers), polyester (e.g., polyester fibers), polyetheretherketone (PPEK) (e.g., PEEK fibers), polyetherketoneketone (PEKK) (e.g., PEKK fibers), glass fibers, and the like. Examples of suitable reinforcement materials include bars (e.g., fiberglass fibers), metal mesh or foil (e.g., expanded metal copper foil), polyacrylonitrile (PAN) (e.g., PAN fibers), electrospun PAN nanofibers, high density wet spun carbon nanotube threads, glass fibers (e.g., E-glass, S-glass), aramid fibers (e.g., Kevlar), fluoropolymer fibers (e.g., ultra high molecular weight polyethylene, high density polyethylene, Teflon, etc.), silicon carbide (e.g., silicon carbide fibers), alumina (e.g., alumina fibers), boron (e.g., boron fibers, such as boron fibers manufactured by Specialty Materials®), hemp (e.g., hemp fibers), quartz (e.g., quartz fibers), ceramics (e.g., ceramic fibers), basalt (e.g., basalt fibers), and combinations or hybrids thereof (e.g., Hexcel HexForce® hybrid reinforcement fibers manufactured by Hexcel® Corporation).

[0016] As mentioned above, the composition of the present disclosure may further contain a polymer matrix or resin. The polymer matrix / resin provides additional strength to the composition of the present disclosure. The matrix material may provide a medium for binding and holding the fiber reinforced sheet and the nanomaterial composite sheet together into a continuous solid. In at least one embodiment, the polymer matrix / resin is selected from polyurethane, epoxy (e.g., Cycom® 977-3 epoxy resin from Cytec Industries, Inc., Woodland Park, New Zealand), thermosetting polymer, thermoplastic polymer, or rubber. The polymer matrix resin of the present disclosure may include at least one of a thermosetting polymer or a thermoplastic polymer. In at least one embodiment, the polymer matrix / resin is at least one of a polyurethane, an epoxy, a bismaleimide, a polyimide, or a polyaryletherketone. Epoxies are thermosetting resins that can provide durable coatings on components, such as vehicle components, such as aircraft components. Bismaleimide resins have desirable deformability and mechanical properties similar to epoxies and can be handled at higher temperatures than epoxies. Polyaryletherketone is a thermosetting resin that can provide the adhesive properties of the composition of the present disclosure to the component, and when the component is a vehicle component, can also withstand the chemical, thermal, and physical conditions to which the vehicle is exposed. Polyimides have a higher breaking strain than thermosetting polymers because thermoplastic polymers can withstand plastic deformation. In at least one embodiment, the composition contains about 1% to about 99% by weight, such as about 50% to about 95% by weight, such as 80% to about 95% by weight, of the polymer matrix or resin based on the total weight of the composition.

[0017] The composition of the present disclosure may further include a dielectric carrier material. The dielectric carrier material may be UHMWPE, a fluoropolymer, a polyimide, or a combination thereof. The dielectric carrier material provides several additional advantages in keeping the lightning strike to the surface and prevents the current from flowing to the underlying composite structure.

[0018] In at least one embodiment, the substrate comprises a component, e.g., a vehicle component, and one or more compositions according to the present disclosure disposed on the component. The composition disposed on the component (e.g., as a layer) is applied at a thickness of about 0.01 μm to about 100 μm, e.g., about 1 μm to about 50 μm, e.g., about 2 μm to about 20 μm, e.g., about 10 μm. Increasing the thickness of the composition increases the resistance, but also adds weight to the composition. The composition of the present disclosure can provide a good balance between electrical properties and overall weight. In at least one embodiment, the resistance of the composition is about 0.1 Ω per square (Ω / □) to about 25 megaΩ per square (MΩ / □), e.g., about 0.5 Ω per square to about 15 megaΩ per square, e.g., about 1 Ω per square to about 10 megaΩ per square, e.g., about 2 Ω per square to about 5 megaΩ per square, e.g., about 3 Ω per square. Conductivity provides static dissipation.

[0019] resistance Resistance measurements can be made using any suitable set of electrodes and measuring equipment (e.g. Keithley 4200 SCS). Resistance measurements can be made by the van der Pauw technique. The four-terminal measurement technique uses parallel sources and sensed measurements of current and voltage across the sample surface. Current and voltage polarities are switched across each junction to test dual polarities. The geometry of the sample is preferably kept constant so that the samples can be directly compared. To account for differences in charge directionality, current and voltage measurements are rotated across each configuration (see Table 1). Table 1. Electrode arrangement configuration for resistance measurements TIFF2025037886000001.tif39170

[0020] Van der Pauw resistance measurements are made by passing a current across two adjacent electrodes and sensing the voltage drop across the sample in a parallel arrangement of electrodes.

[0021] The sheet resistance can be calculated for a given composition from the ratio of V to I. For samples that exhibit strictly isotropic resistivity, R A =R B =R C =R D In the case of isotropic resistance, for example, R A =R B In the case of R , the sheet resistance is determined by the average of the two measured resistances (see Equation 1 below). For samples with anisotropic resistance (different resistance in the x and y directions), the calculation of the sheet resistance becomes more complicated, but this will be discussed in the following paragraphs. A ≠R C and R B ≠R D For all samples where , the measurement is invalid. Equation 2 shows how to determine the bulk resistivity ρ when the thickness d of the composition is known (resistivity is usually expressed in Ω·cm, so d is used in cm), and this equation is derived from the original Van der Pauw theorem. The bulk resistivity ρ can be used to calculate the electrical conductivity σ (S·cm-1), which is inversely proportional (Equation 2). equation 1 TIFF2025037886000002.tif14170 equation 2 TIFF2025037886000003.tif14170

[0022] R A ≠R BIn the case of , it becomes more difficult to determine the value of electrical conductivity from the Van der Pauw equation. If the electrical conductivity is not isotropic, the electrical conductivity is a tensor value with x, y and z directions. For very thin compositions, an accurate electrical conductivity value can be obtained by taking the square root of the product of orthogonal electrical conductivity measurements (see Equation 3 below). This calculation is only true if the measurements are aligned with the electrical conductivity tensor axis. It is assumed that the larger of the two resistances measured by this technique is exactly aligned with the minimum electrical conductivity tensor and the smaller of the resistance measurements is exactly aligned with the maximum electrical conductivity tensor. If the electrical conductivity tensor and the electrode / sample orientation are not aligned, an inaccurate electrical conductivity measurement will result. equation 3 TIFF2025037886000004.tif12170

[0023] For van der Pauw measurement chips, the numbers correspond to the axes of measurement and are labeled Sigma X (σ A , σ B and σ C ) represents the conductivity tensor direction. If the sample axes and the tensor axes are not aligned, the measured conductivity will be inaccurate. The van der Pauw printed electrodes (with a Keithley 4200 SCS) provide a suitable device testbed for measuring samples.

[0024] As a measure to control humidity effects on the measurements, a small sample station may be used to perform accurate van der Pauw measurements with Dropsens off-the-shelf electrodes, which are only connected to a Keithley 4200 SCS.

[0025] composite material In at least one example, the composition of the present disclosure contains a polymer matrix / resin and is a composite, which will be described in more detail below. A composite is a solid material having at least two phase-separated components with different inherent properties. The composite can be, for example, a three-dimensional structure of fibers according to the present disclosure mixed together (e.g., woven), a unidirectional tape, or a single ply of material. The composite can have a composite structure selected from a mat, a tow, a laminate (layered structure or ply), a braid, or a filament. The composite provides improved conductivity in multiple directions, uniform tensile properties and impact strength, and improved electrical uniformity (compared to unidirectional fibers).

[0026] metal base material In at least one embodiment, a metal substrate comprises a composition of the present disclosure disposed thereon. Metal substrates include steel, aluminum, titanium, magnesium, tantalum, copper, and alloys thereof. The composition can be disposed (directly or indirectly) on the metal substrate. The composition (disposed on the metal substrate) can have a thickness of about 1 micron to about 1 millimeter, such as a thickness of about 1 micron to about 100 microns, such as a thickness of about 1 micron to about 10 microns. The thickness of the composition according to the present disclosure disposed on the substrate can be thin enough not to significantly increase the weight of the coated substrate, yet still provide a suitable amount of the composition to obtain other benefits, such as protection from substrate corrosion. The metal substrate can be or form a vehicle component, or can be or form a component of a vehicle component. The vehicle component is a component of a vehicle, such as a structural component of an aircraft, such as one or more landing gears, panels, or joints. Examples of vehicle components include rotors, landing gear, auxiliary power units, aircraft noses, fuel tanks, tail cones, panels, coated lap joints between two or more panels, wing-fuselage assemblies, structural aircraft composites, fuselage-body joints, wing rib-skin joints, and / or other interior components.

[0027] Figure 1 is an aircraft comprising vehicle components according to at least one embodiment of the present disclosure. As shown in Figure 1, the aircraft 100 comprises an aircraft structure 102 including vehicle components such as an elongated fuselage 104, wings 106 extending laterally from the fuselage 104, and empennage 108 extending longitudinally from the fuselage 104. A composition of the present disclosure may be disposed on one or more surfaces of these aircraft components, thereby forming one or more aircraft components comprising the composition on a surface thereof.

[0028] Alternatively, the compositions of the present disclosure may be disposed on one or more components of, for example, a wind turbine, a satellite, or other vehicle, such as a car, a boat, or the like.

[0029] Fiber composition In at least one embodiment, the fibers of the composition of the present disclosure (of the metal-coated fibers) can include carbon fibers, such as graphene, graphite, and carbon nanotubes. Carbon fibers provide a lightweight yet strong fiber material. FIG. 2 is a flow diagram of a method 200 for manufacturing a component, such as a vehicle component, in which the composition of the present disclosure is disposed. For example, graphite can be manufactured from polyacrylonitrile fibers. As shown in block 202, the method 200 includes manufacturing polyacrylonitrile (PAN) (acrylic textile fiber) by wet or dry spinning a polyacrylonitrile (PAN) polymer. Dry spinning produces round, smooth fibers, whereas wet spinning (extrusion into a coagulation bath) produces a variety of "non-circular" cross sections, including dog-bone, oval, and kidney bean cross sections. These non-circular cross sections provide a high relative surface area and improve effective bonding. These fibers can stretch during the spinning process. The greater the elongation, the smaller the fiber diameter and the greater the preferred orientation of the molecular chains along the fiber axis, resulting in a stiffer carbon fiber during processing. 3 Book fiber ~ approx. 105 Book fibers, e.g., about 10 4 The fibers can include a single strand of fibers. To form carbon fibers (e.g., graphite), PAN is first stabilized by oxidation in air at about 250°C. At this point, PAN has a sufficient glass transition temperature (Tg) to withstand melting at higher temperatures. To prevent the fibers from shrinking during oxidation, such fibers are held in tension during stabilization, which further aligns the ladder structure with the fiber axis through the resulting deformation. The material is then carbonized at temperatures of about 1200°C to 1600°C in an inert atmosphere, e.g., an inert gas, e.g., nitrogen. As this heat treatment progresses, aromatic benzene rings bond to form polynuclear aromatic fragments (e.g., structures more similar to graphene). The aromatic network gradually transforms into mostly carbon atoms, becoming more dense through cross-linking, and N2 evolving through vents in the fiber. When heat treatment is performed at 1500-1600°C, the tensile strength of the fiber exceeds 1.5% for a mean Young's modulus of about 240 GPa.

[0030] If a higher modulus is desired (which would result in a lower strength and tensile strength of the fiber), the fiber can be subjected to a final graphitization stage of heat treatment. As shown in block 204, the method 200 includes introducing the fiber into a furnace (e.g., a graphitization furnace) and heating the furnace to a temperature of about 2,000° C. to about 2,700° C., e.g., about 2500° C. The graphitization heat treatment can be performed in an inert atmosphere, e.g., an inert gas, e.g., argon, which reduces or prevents the formation of defects in the fiber. During this process, the basal plane layers of aromatic carbon grow and adjacent layers further fuse together into a fiber having a graphitic shape, thereby increasing the planar orientation of the fiber and thus increasing the elastic modulus (e.g., about 300 GPa to about 400 GPa, e.g., about 380 GPa) compared to fiber material that has not undergone this graphitization heat treatment. Such fibers (e.g., carbon fibers) may have filament diameters of about 1 μm to about 20 μm, e.g., about 8 μm, and may have filament diameters of about 2×10 4 1000 pieces of filament ~ approx. 3 x 10 4 1000 pieces of filament, e.g. 2.5×10 4The fibers (e.g., carbon fibers) of the present disclosure may have a thickness of about 1 μm to about 1 mm, for example, about 1 μm to about 10 μm, and a density of about 0.5 g / cm 3 ~Approx. 1g / cm 3 , for example, about 0.7 g / cm 3 It may be.

[0031] As previously mentioned, the fibers of the present disclosure are metal coated fibers. As shown in block 206, the method 200 includes coating the fiber with a metal. The metal can be disposed on the fibers of the present disclosure by any suitable metal deposition method. In at least one embodiment, the metal is disposed on the fiber by immersion, chemical vapor deposition, or plating (e.g., electroless plating). The metal coating can have a thickness of 0.5 microns to about 20 millimeters, such as a thickness of about 0.5 microns to 100 microns, such as a thickness of 1 micron to 5 microns.

[0032] In at least one example, the metal is deposited on the fiber by autocatalytic (electroless) plating (a plating process in which deposition occurs without the application of electrical current). The process is a chemical reaction and is autocatalytic. The deposition rate is typically 12.5 μm to 25 μm. Although thicknesses up to 650 μm may be achieved, the coating is usually less than 50 μm in practice due to the slow deposition rate. Because no electric field is present, the thickness of the electroless plating tends to be more uniform than that of electrolytic plating. For example, nickel and copper can be used in electroless plating. In the case of nickel, the deposit is dense, relatively hard (43-55 HRC, rising to approximately 65 HRC after 2 hours at 343° C.), and brittle.

[0033] Coating of metal-coated textiles As shown in block 208, the method 200 includes coating the metal coated fiber with a conductive polymer. Coating the fiber may include a template polymerization coating method or a polymer coating method.

[0034] Template Polymerization Coating: When attempting to mix a conductive polymer with metal-coated fibers, it has traditionally been difficult to separate the coated fibers from excess conductive polymer (e.g., conductive polymer that was not disposed near the metal-coated fibers). However, in template polymerization coating methods, a monomer is polymerized in the presence of the metal-coated fibers to form a polymer in-situ that is disposed on the metal-coated fibers.

[0035] Figure 3 is a flow diagram illustrating a method 300 for coating a metal-coated fiber with a conductive polymer by template polymerization. As shown in Figure 3, the method 300 includes contacting 302 the metal-coated fiber material with an oxidizing agent and a monomer to form a first composition containing the metal-coated fiber material and the conductive polymer. The method 300 includes contacting 304 the first composition with a polymer matrix or resin to form a second composition.

[0036] In at least one embodiment, the surface of the metal coated fiber is oxidized with an oxidizing agent during or prior to the polymerization of the monomer. Polymerization of the monomer forms a polymer disposed on the surface (e.g., the oxidized surface) of the metal coated fiber. The oxidizing agent can be any suitable oxidizing agent capable of oxidizing a neutral metal or alloy surface. The oxidizing agent can include an iron-containing oxidizing agent, a cerium-containing oxidizing agent, or a sodium-containing oxidizing agent. The oxidizing agent used can be selected based on the strength of its oxidizing power. For example, iron-containing oxidizing agents are typically stronger oxidants for metal surfaces than sodium-containing oxidizing agents. Stronger oxidizing agents can oxidize metal surfaces more quickly (e.g., by soaking and rinsing) than weaker oxidizing agents, but care must be taken not to over-oxidize the metal by exposing it to the strong oxidizing agent for too long. In at least one embodiment, the iron-containing oxidizing agent can be selected from the group consisting of iron-para-toluenesulfonate (Fe(III)-(PTSA)3), iron permanganate (Fe(III)-(MnO4), and iron-para-toluenesulfonate (Fe(III)-(MnO4). - )3), ferric nitrate, ferrous sulfate (Fe(III)2(SO4)3), ferric dichromate (Fe(III)2(CrO4)3), or mixtures thereof. In at least one embodiment, the cerium-containing oxidizer is selected from cerium (IV) sulfate, ammonium cerium (IV) nitrate, or mixtures thereof. In at least one embodiment, the sodium-containing oxidizer is selected from sodium dichromate (Na2Cr2O7), NaOCl (bleach), sodium chlorate, sodium chlorite, sodium dichloroiodate, sodium nitrite, sodium perborate, sodium percarbonate, sodium periodate, sodium peroxydisulfate, or mixtures thereof.

[0037] In at least one embodiment, the oxidizing agent is a potassium-containing oxidizing agent, which can be selected from potassium ferricyanide, potassium permanganate, potassium peroxydisulfate, potassium peroxymonosulfate, or mixtures thereof.

[0038] The oxidizing agent can be ammonium persulfate ((NH4)2S2O8). Other examples of oxidizing agents include benzoyl peroxide, tert-butyl hydroperoxide, tert-butyl hypochlorite, tert-butyl nitrite, carbon tetrabromide, chloramine-T, chloranil, chloromethyl-4-fluoro-1,4-diazoniabicyclo[2.2.2]octane bis(tetrafluoroborate), 3-chloroperoxybenzoic acid, chromium trioxide, hydrogen peroxide, hydrogen peroxide urea adduct, iodine (I2), manganese (IV) oxide, osmium tetroxide, oxone, ozone, peracetic acid, periodic acid, peracid, tert-butyl hydroperoxide, vanadium pentoxide, tert-butyl hypochlorite, or mixtures thereof.

[0039] The oxidizing agent can be contacted with the metal-coated fiber to form an oxidized metal-coated fiber. Prior to contacting the oxidizing agent with the metal-coated fiber, the oxidizing agent or the metal-coated fiber can be placed in a solvent, such as isopropyl alcohol or acetonitrile. In at least one embodiment, the concentration of the oxidizing agent in the solvent is about 1 w / w to about 50 w / w, such as about 5 w / w to about 25 w / w, such as about 7% w / w to about 12% w / w, such as about 8% w / w. To form an oxidized metal-coated fiber, the metal-coated fiber can be in a solution. The concentration of the metal-coated fiber in the solvent / solution can be about 1 w / w to about 50 w / w, such as about 5 w / w to about 25 w / w, such as about 10% w / w to about 20% w / w, such as about 15% w / w. The solution of the oxidizing agent and the metal-coated fiber are mixed and optionally heated. Heating can be performed at a temperature of about 20° C. to about 150° C., for example, at a temperature of about 40° C. to about 80° C., for example, at a temperature of about 60° C. Mixing can be performed for about 1 hour to about 72 hours, for example, about 12 hours to about 48 hours, for example, about 20 hours to about 30 hours, for example, about 24 hours. The oxidized metal-coated fibers can be precipitated from the solution, filtered and dried.

[0040] Alternatively, the oxidized metal-coated fiber can be formed by contacting an oxidizing agent with a metal-coated fiber to form a contact product (e.g., a mixture) and roller milling the contact product. The roller milling can be performed for about 1 hour to about 72 hours, such as about 10 hours to about 36 hours, such as about 24 hours. Prior to contacting the oxidizing agent with the metal-coated fiber, the oxidizing agent or the metal-coated fiber can be placed in a solvent, such as isopropyl alcohol or acetonitrile. In at least one embodiment, the concentration of the oxidizing agent in the solvent is about 1 w / w to about 50 w / w, such as about 5 w / w to about 25 w / w, such as about 7% w / w to about 12% w / w, such as about 8% w / w. To form the oxidized metal-coated fiber, the metal-coated fiber can be included in a solution. The concentration of the metal coated fibers in the solvent / solution may be from about 1 w / w to about 50 w / w, such as from about 5 w / w to about 25 w / w, such as from about 10% w / w to about 20% w / w, such as about 15% w / w.

[0041] The oxidized metal coated fiber is contacted with a monomer to form a composition containing the metal coated fiber having a polymer disposed thereon. In at least one embodiment, the monomer is 3,4-ethylenedioxythiophene (EDOT) (which polymerizes to form poly(3,4-ethylenedioxythiophene)), aniline (which polymerizes to form polyaniline), pyrrole (which polymerizes to form polypyrrole), and derivatives or mixtures thereof. The monomer can be placed in a solvent, such as butyl acetate, prior to contacting the oxidized metal coated fiber with the monomer. The oxidized metal coated fiber can be placed in a solution of the monomer. The solution can be mixed and optionally heated. Mixing can be performed for about 1 minute to about 24 hours, such as 10 minutes to about 6 hours, such as about 1 hour to about 3 hours, such as about 2 hours. Heating can be performed for about 20° C. to about 15 hours. The heating can be carried out at a temperature of about 0°C, for example at a temperature of about 40°C to about 80°C, for example at a temperature of about 60°C. The metal-coated fiber having the polymer disposed thereon can be precipitated from the solution, filtered and dried (for example by heat under vacuum, for example at about 60°C). Alternatively, the solution can be roller milled and optionally heated. The roller milling can be carried out for about 1 minute to about 72 hours, for example 6 hours to about 36 hours, for example about 10 hours to about 24 hours, for example about 19 hours. The heating can be carried out at a temperature of about 20°C to about 150°C, for example at a temperature of about 40°C to about 80°C, for example at a temperature of about 60°C. The metal-coated fiber having the polymer disposed thereon can be dried (for example by heat under vacuum, for example at about 60°C).

[0042] Polymer Coating Method: In the polymer coating method, a polymer is contacted with a metal-coated fiber (which may be neutral or oxidized) without the use of a monomer to form a polymer on the metal-coated fiber. When a conductive polymer is mixed with a metal-coated fiber, it is difficult to separate the coated fiber from excess conductive polymer (e.g., conductive polymer that was not placed near the metal-coated fiber), but it has been found that some conductive polymers, such as polyaniline and PEDOT-PSS (PSS=polystyrene sulfonate), can be placed on the metal-coated fiber by the polymer coating method of the present disclosure.

[0043] The polymer coating includes contacting a conductive polymer with a metal-coated fiber to form a metal-coated fiber having a polymer disposed thereon. The polymer coating includes placing the conductive polymer or metal-coated fiber in a solvent, such as water, isopropyl alcohol, acetonitrile, or butyl acetate, to form a solution. The conductive polymer or metal-coated fiber is then placed in the solution and mixed. In at least one embodiment, the mixing includes subjecting the solution including the conductive polymer and the metal-coated fiber to ultrasonic treatment. The mixing can be performed for about 30 seconds to about 72 hours, such as about 1 minute to about 1 hour, such as about 1 minute to about 30 minutes, such as about 1 minute to about 10 minutes, such as about 5 minutes. The solvent is then evaporated, and the metal-coated fiber having a polymer disposed thereon is dried, optionally by heating (e.g., at a temperature of about 70° C.).

[0044] Fiber Composite Composition At block 210, the method 200 includes disposing the (polymer+metal) coated fibers in a fiber-containing composite. (Alternatively, the metal coated fibers are disposed in the composite prior to the conductive polymer coating process). The composite may have a mat, tow, laminate (layered structure or ply), braid, or filament as a composite structure. The composite may have a sufficient concentration of fibers oriented in one or more directions during the manufacture of the vehicle component to provide the desired strength and stiffness in the cured product form. The fiber tows may be woven into a fabric, for example a plain or satin weave fabric. For in-plain loading, a laminate or ply structure may be used, including layers or stacks of unidirectionally or bidirectionally oriented fibers. Alternatively, the fibers may be disposed by one or more textile techniques, for example weaving, braiding, or filament winding.

[0045] Thus, to obtain the desired mechanical properties for the fibers, the fiber layers or plies in the laminate are oriented at an angle of about 0° to about 90° relative to the initial fill direction of 0°. In at least one embodiment, the fiber mat has a combination of 0° orientation, ±45° orientation, and 90° orientation, which reduces or prevents distortion of the components after curing and when loaded in use. The laminate is very stiff and strong in the direction of highest fiber concentration at 0° (in the plane), and the laminate is said to be orthotropic.

[0046] If the ply configuration is made with equal numbers of plies at 0°±60° or 0°±45° and 90°, the planar mechanical properties do not vary significantly with the fill direction, in which case the composite is said to be quasi-isotropic. Quasi-isotropic configurations are also used where local stresses are high, e.g. in mechanical joints, since the stress concentration factors are similar to isotropic materials.

[0047] In at least one embodiment, the fiber composite is woven with one or more additional fibers / composites. The additional fibers include glass fibers or aramid fibers. In at least one embodiment, the one or more additional fibers are woven in the 0° or warp direction (winding direction) or in the 90° (weft) direction.

[0048] In at least one embodiment, forming a fiber composite includes holding the carbon fibers in a stationary position by the knitting yarn during weaving to prevent the fibers from curling (waving). These non-curling fabrics can include 0°, 90°, and / or ±45° oriented fibers in any desired proportion. Because fiber waving is reduced or eliminated, composites based on non-curling fabrics have significantly improved compressive strength compared to composites based on woven materials. Stiffness in both tension and compression is also improved by about 10% compared to composites based on woven materials.

[0049] Composite and component composition At block 212, the method 200 includes combining a first composition (e.g., a fiber composite) with a polymer matrix / resin to form a second composition. The first composition includes metal-coated fibers having a polymer disposed thereon. The combining includes impregnating a fiber composite of the present disclosure with a liquid polymer matrix / resin and then curing / solidifying the polymer matrix / resin (e.g., by heating or cooling) to form a continuous solid matrix. For example, a thermosetting polymer is cured by heating or a thermoplastic resin is crystallized by cooling. Alternatively, a fiber or fiber composite (e.g., a fiber tow, or a sheet of aligned fibers) is coated or mixed with a solid polymer matrix / resin or polymer matrix / resin precursor and the second composition is formed by flowing (and curing, if necessary) with the coating under heat and pressure.

[0050] In at least one embodiment, the polymer is a thermosetting or thermoplastic polymer. Thermosetting polymers are long chain molecules that harden by crosslinking, forming a three-dimensional network that is not easily melted or reshaped. Such polymers allow composites to be made at relatively low temperatures and pressures because they go through a low viscosity stage before polymerization and crosslinking (if it occurs). In at least one embodiment, the polymer matrix resin is at least one of an epoxy, a bismaleimide, or a polyaryletherketone (e.g., polyetheretherketone or polyetherketone).

[0051] Epoxies have sufficient mechanical properties for use, for example, in aircraft coatings and other applications where mechanical properties may be important, and they shrink little and form adequate bonds with fibers. Epoxies go through a low viscosity stage during cure, allowing the use of liquid resin molding techniques, such as resin transfer molding. Epoxy-containing compositions that cure at 120°C and 180°C can have maximum use temperatures of about 100 to about 150°C.

[0052] Bismaleimide resins have desirable deformability and mechanical properties similar to epoxies, but can be handled at higher temperatures than epoxies. Bismaleimide-containing compositions that cure at about 200°C can have maximum use temperatures in excess of 180°C.

[0053] The polymer matrix / resin of the present disclosure can be a thermoplastic polymer. Thermoplastic polymers are linear (non-crosslinked) polymers that can be melted and reshaped. High performance thermoplastics for use as aircraft coatings include polymers such as polyetheretherketone (curable up to about 120°C), polyetherketone (curable up to about 145°C), and polyimide (curable up to about 270°C). Thermoplastic polymers are advantageous because they have higher strain to break than thermosetting polymers and can withstand plastic deformation.

[0054] Thermoplastic polymers are easy to polymerize and can form very viscous liquids when melted. Fabrication techniques can be based on resin film (or resin fiber) infusion and prepreg techniques. Fibers are coated with polymer (from a solvent solution) and the resulting part is then consolidated at high temperature and pressure. Alternatively, sheets of thermoplastic film can be layered between sheets of dry fiber, or thermoplastic fibers can be woven with carbon fibers and the composite consolidated by hot pressing. Furthermore, thermoplastics absorb very little water and therefore have better hot / wet property retention than thermoset composites, but high temperature processing is required in practice.

[0055] The polymer matrix / resin of the present disclosure can shape the composition, transfer loads to and from the fibers, separate the fibers so that if one fiber fails, adjacent fibers are protected, and / or protect the fibers from the surrounding environment. The fibers can interact with (e.g., bond to) the polymer matrix / resin to provide toughness to the overall composition. The location or locations where the fibers interact with the polymer are sometimes referred to as the interface or interphase.

[0056] Combining fibers or fiber composites with a polymer resin / matrix to form the compositions of the present disclosure involves impregnating or coating (e.g., dipping or spraying) the fibers with a liquid polymer to form a mixture and then curing. This is sometimes called resin transfer molding and can be used, for example, when the polymer has a low viscosity (e.g., less than 1,000 centipoise (cps)).

[0057] Alternatively, combining the fibers (or fiber composite) with a polymer matrix / resin to form the composition of the present disclosure involves infusing a molten polymer film into the fibers (or fiber mat) under pressure and then curing, which is sometimes referred to as resin film infusion.

[0058] Alternatively, combining the fibers (or fiber composites) of the present disclosure with a polymer resin / matrix to form a composite may involve pre-impregnating bundles or tows of fiber sheets with liquid resin (prepreg) followed by alignment (stack), followed by consolidation and curing under temperature and pressure. Starting at room temperature for a thermosetting composite, the temperature can be increased to a temperature of about 350° F., the ambient pressure increased (e.g., to about 200 psi), and the high temperature, high pressure conditions maintained for up to several hours depending on the material, then allowed to come to room temperature / atmospheric pressure.

[0059] In at least one embodiment, a plurality of cured composites (e.g., metal coated fibers having polymer disposed thereon and impregnated or coated with a liquid polymer matrix / resin) are stacked and consolidated at room temperature of about 250°F to about 600°F to form a consolidated composition.

[0060] As shown in block 214, the method 200 includes depositing the composition of the present disclosure onto a metal substrate. Metal substrates include steel, aluminum, titanium, magnesium, tantalum, copper, and alloys thereof. Deposition may include any suitable "lay-up" or "collation" method known in the art. For example, the composition of the present disclosure may be cut to conform to the shape of the metal substrate and deposited onto the metal. The deposited composition is "debulked" by placing it into a vacuum bag and pumping to a pressure of 980 mbar or less for about 1 minute to about 30 minutes. The composition may be deposited as tiles or as a continuous piece. A breather material may be used and the breather material may be connected to the vacuum portion of the vacuum bag.

[0061] At block 216, the composition is cured to produce a component, such as a coated vehicle component of a vehicle, such as a coated vehicle component of an aircraft, car, train, watercraft, or wind turbine. In at least one embodiment, the composition of the present disclosure is cured at a temperature of about 20° C. to about 300° C., such as a temperature of about 100° C. to about 200° C. The vehicle component is any suitable component of a vehicle, such as a structural component, such as one or more landing gears, panels, or joints of an aircraft. Examples of vehicle components include rotors, auxiliary power units, aircraft noses, fuel tanks, tail cones, panels, coated lap joints between two or more panels, wing-fuselage assemblies, structural aircraft composites, fuselage-body joints, wing rib-skin joints, and / or other interior components. In at least one embodiment, the vehicle is an aircraft, car, train, or watercraft. In at least one embodiment, the component is a wind turbine component.

[0062] FIG. 4 is a flow diagram of a method 400 for manufacturing a component having a composition disposed thereon of the present disclosure. As shown in FIG. 4, the method 400 includes introducing fibers into a furnace (block 402), introducing an inert gas into the furnace (block 404), and heating the furnace to a temperature of about 2,000° C. to about 2,700° C. (block 406). The method 400 includes contacting a metal-coated fiber material with a conductive polymer to form a first composition including metal-coated fibers having a conductive polymer disposed thereon (block 408). The method 400 includes mixing the first composition with a polymer matrix resin to form a second composition (block 410). The method 400 includes depositing the second composition onto a metal substrate (block 412). The method 400 includes curing the second composition at a temperature of about 20° C. to about 300° C. (block 414).

[0063] Aspects Clause 1 A conductive polymer; a textile material having one or more metals disposed thereon; A composition comprising: Clause 2 2. The composition of claim 1, further comprising a polymer matrix or resin. Clause 3 3. The composition of claim 1 or 2, comprising about 50% to about 99% by weight of the polymer matrix or resin, based on the total weight of the composition. Clause 4 4. The composition of any of clauses 1 to 3, wherein the conductive polymer is selected from polyaniline, poly(ethylenedioxythiophene), polypyrrole, or a mixture thereof. Clause 5 5. The composition of any of clauses 1 to 4, comprising conductive polymer and metal coated fibers at a loading of about 1% to about 30% by weight, based on the total weight of the composition. Clause 6 6. The composition of any of clauses 1 to 5, wherein the metal is selected from nickel, titanium, palladium, iron, cobalt, copper, aluminum, chromium, or mixtures thereof. Clause 7 7. The composition of any of clauses 1 to 6, wherein the ratio of conductive polymer to metal coated fiber is from about 0.002:1 to about 4:1. Clause 8 8. The composition of any of clauses 1 to 7, wherein the fibers are selected from carbon, nylon, glass fibers, polyacrylonitrile, or combinations thereof. Clause 9 9. The composition of any of clauses 1-8, wherein the polymer matrix or resin is selected from polyurethane, epoxy, thermoset polymer, thermoplastic polymer, rubber, bismaleimide, polyimide, polyaryletherketone, or combinations thereof. Clause 10 10. The composition of any of clauses 1-9, wherein the polymer matrix or resin is an epoxy. Clause 11 11. The composition of any of clauses 1 to 10, which is a composite. Clause 12 12. The composition of any of clauses 1-11, wherein the composite is disposed on the component, the composite having a thickness of from 0.01 μm to about 100 μm. Clause 13 13. The composition of any of clauses 1-12, having a resistance of about 0.01 ohms per square (Ω / □) to about 25 MΩ / □. Clause 14 14. The component of any of clauses 1-13, wherein the component is a vehicle component. Clause 15 15. The composition of claim 14, wherein the vehicle component is a rotor, a landing gear, an auxiliary power unit, an aircraft nose, a fuel tank, a tail cone, a panel, a coated lap joint between two or more panels, a wing-fuselage assembly, a structural aircraft composite, a fuselage-body joint, or a wing rib-skin joint. Clause 16 contacting the metal-coated fiber material with an oxidizing agent and a monomer to form a first composition containing the metal-coated fiber material and a conductive polymer; and contacting the first composition with a polymer matrix or resin to form a second composition; A method for manufacturing a component, comprising: Clause 17 17. The method of claim 16, wherein the oxidizing agent is an iron-containing oxidizing agent, a cerium-containing oxidizing agent, or a sodium-containing oxidizing agent. Clause 18 18. The method of claim 16 or 17, wherein the oxidizing agent is selected from iron paratoluenesulfonate, iron permanganate, iron sulfate, iron dichromate, cerium (IV) sulfate, sodium dichromate, ammonium persulfate, or a mixture thereof. Clause 19 19. The method of any of clauses 16-18, further comprising heating the first composition to a temperature of about 40° C. to about 80° C. Clause 20 20. The method of any of clauses 16-19, further comprising heating the second composition to a temperature of about 40°C to about 80°C. Clause 21 21. The method of any of clauses 16 to 20, wherein the conductive polymer is selected from polyaniline, poly(ethylenedioxythiophene), polypyrrole, or a mixture thereof. Clause 22 22. The method according to any of clauses 16 to 21, wherein the metal is selected from nickel, titanium, palladium, iron, cobalt, copper, aluminium, chromium or mixtures thereof. Clause 23 23. The method of any of clauses 16 to 22, wherein the fibers are selected from carbon, nylon, glass fibers, polyacrylonitrile, or combinations thereof.

[0064] Working Example The electrical conductivity of typical metal coated fibers in a matrix resin is dependent on the aspect ratio of the fibers and percolation which depends on the % loading. It has been found that conductive polymer coatings can bridge the fibers, resulting in higher electrical conductivity and lower loading of the fibers into the composition (e.g. composite).

[0065] Materials: 3,4-Ethylenedioxythiophene (97%, Alfa Aesar) (EDOT); iron(III)(p-toluenesulfonate) (Fe(III)(PTSA)3) (Sigma); butyl acetate (BuAc) (Sigma); isopropanol (IPA); PEDOT-PSSA (Clevios); PR1664 Polyurethane (PPG), Parts A and B.

[0066] Precursor 1. Poly(3,4-ethylenedioxythiophene) p-toluenesulfonate (PEDOT-PTSA) coated NiCF Step 1 An 8.3% w / w FePTSA-IPA solution was prepared by dissolving 7.3 grams of FePTSA in 81.1 grams of IPA. A 19.8% w / w EDOT solution in BuAc was prepared by dissolving 22.1 grams of EDOT in 89.8 grams of BuAc.

[0067] 1.87 grams of NiCF were dispersed in 11.45 grams of FePTSA solution using a vortex mixer. It was then heated on a hot plate at 60° C. with stirring for 24 hours. 2.29 grams of NiCF-Fe-PTSA powder was collected by vacuum filtration and air dried. Figure 6A shows the raw energy dispersive X-ray spectroscopy (EDS) spectrum of NiCF. Figure 6B shows the energy dispersive X-ray spectroscopy (EDS) spectrum of NiCF-Fe-PTSA.

[0068] Then, 36.72 grams of EDOT solution was added to 2.29 grams of NiCF-Fe-PTSA and heated with stirring at 60° C. for 2 hours. 2.02 grams of PEDOT-coated NiCF were collected by vacuum filtration and dried under vacuum at 60° C. Figure 6C shows the energy dispersive X-ray spectroscopy (EDS) spectrum of PEDOT-NiCF. The solid line in Figure 6C is the average of all the data.

[0069] Fourier transform infrared spectroscopy (FTIR) spectra of PEDOT-NiCF and NiCF are shown in FIG. 5 (overlapped spectra of NiCF (bold curve) and PEDOT-NiCF (thin curve). The FTIR spectrum shows the formation of a PEDOT-PTSA coating on NiCF.

[0070] Step 2 7.0 grams of FePTSA was dissolved in 73 grams of acetonitrile. 18.1 grams of NiCF4 was added to the solution to form a second solution which was placed on a roller mill for 24 hours. The product was collected by vacuum filtration, washed three times with acetonitrile, and air dried. 21.52 grams of product (FeNiCF4) was collected.

[0071] 24.3 grams of EDOT was dissolved in 101.6 grams of butyl acetate. Then, 5.24 grams of FeNiCF prepared above was mixed into 105.4 grams of EDOT solution to form a second solution, which was roller milled for 19 hours. After drying at 70°C for 24 hours, 5.08 grams of product (PEDOT-NiCF) was recovered by vacuum filtration. FTIR spectrum (not shown) was obtained and also showed a PEDOT-PTSA coating on NiCF.

[0072] 2. Poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT-PSSA) coated NiCF 10 grams of PEDOT-PSSA (Clevios PHC V4, available from HC Starck GmbH) was dissolved in 400 ml of deionized water. 1 gram of NiCF was added to 7.5 grams of the PEDOT-PSSA solution to form a second solution. This mixture was sonicated for 5 minutes, placed on a watch glass, and air-dried at 71° C. The PEDOT appeared to be significantly accumulated (a "glob" or "gel") on the NiCF.

[0073] FTIR spectra (not shown) were obtained for the recovered PEDOT-PSSA NiCF, but no peaks characteristic of PEDOT were observed, likely due to the significant accumulation of polymer on the NiCF, highlighting the advantage of the template polymerization method of the present disclosure.

[0074] Resistance measurement The powder was carefully spread to cover the serpentine electrical circuit and the measured resistance (R) is given in ohms in Table 1. Table 1 TIFF2025037886000005.tif128170

[0075] The films were cast onto microscope slides and the resistance was measured (ohms / square) using a resistance meter. The thickness of the two films was nearly the same, so the data indicates that the conductivity of the film increased by about three times.

[0076] JMP 13 analysis The JMP analysis is a method for determining whether differences in responses are statistically significant. JMP is a division of SAS, Campus Drive, Cary, NC 27513, version 13 software was used.

[0077] JMP Analysis is a tool for investigating the relationship between a continuous variable Y and categorical X variables. By fitting Y to the Oneway, or X Platform, we can investigate how the distribution of a continuous variable Y differs across groups defined by one categorical X variable. For example, we may want to know how different categories of the same drug X affect a patient's pain level on a numerical scale (Y). The Oneway Platform is continuous due to the nominal or ordinal nature of fitting Y to the X Platform. The results of the analysis are presented as plots, and cross-sectional and further analyses can be performed, for example: oneway analysis of variables to find means and test whether they are equal; non-parametric tests; tests for homogeneity of variance of variables; multiple comparison tests on means with comparison circles; box plots of outliers overlaid by group; power details for Oneway ANOVA, etc.

[0078] One-Way JMP Analysis Overview In a one-way analysis of variables, differences between group means are examined. The total variable in the response is divided into two parts: the within-groups variable and the between-groups variable. If the between-groups variable is greater than the within-groups variable, the difference between the group means is considered significant.

[0079] JMP analysis of PEDOT-PTS-NiCF 7 shows the JMP analysis readout for the examples of the present disclosure. The JMP data analysis for the examples of the present disclosure shows that the resistance of the PEDOT-PTS-NiCF materials synthesized by procedures 1 and 2 is statistically significantly lower (by a factor of nearly three) compared to NiCF (by Tukey Kramer analysis).

[0080] Preparation of NiCF in a polyurethane matrix 1.5 grams of PR1664 (Part B) was dissolved in 1.8 grams of dimethyl carbonate (DMC). 1.5 grams of NiCF powder was then added to the DMC solution and mixed in the Thinky mixer. 0.3 grams of PR1664 (Part A) was added to the NiCF dispersion and mixed again in the Thinky mixer. This coating method provided effective mixing into the polyurethane matrix and was used for both modified and unmodified NiCF.

[0081] Table 2 shows the measured resistance for different loadings of NiCF and optional conductive polymer (total loadings range from 5% to 20% by weight) disposed in polyurethane. Coating of NiCF with polyaniline was performed by mixing the NiCF with PANI dissolved in toluene (which was then removed). TIFF2025037886000007.tif123170

[0082] Coating of NiCF with PEDOT-PTSA was demonstrated by oxidative surface polymerization (template polymerization). The resulting coating was found to enhance the conductivity of NiCF powder by a factor of three. This novel structure allows for the formulation of higher electrical conductivity per gram of NiCF, as well as lighter coatings with enhanced electrical properties.

[0083] Additionally, the disclosure includes examples according to the following provisions: Clause 1 A composition comprising a conductive polymer and a fibrous material having one or more metals disposed thereon. Clause 2 2. The composition of claim 1, further comprising a polymer matrix or resin. Clause 3 3. The composition of claim 2, comprising about 50% to about 99% by weight of the polymer matrix or resin, based on the total weight of the composition. Clause 4 4. The composition of any of clauses 1 to 3, wherein the conductive polymer is selected from polyaniline, poly(ethylenedioxythiophene), polypyrrole, or a mixture thereof. Clause 5 3. The composition of claim 2, comprising a conductive polymer and metal coated fibers at a loading of about 1% to about 20% by weight, based on the total weight of the composition. Clause 6 6. The composition of claim 5, wherein the metal is selected from nickel, titanium, palladium, iron, cobalt, copper, aluminum, chromium, or mixtures thereof. Clause 7 7. The composition of claim 6, wherein the ratio of conductive polymer to metal coated fiber is from about 0.002:1 to about 4:1. Clause 8 8. The composition of any one of clauses 1 to 7, wherein the fibers are selected from carbon, nylon, glass fibers, polyacrylonitrile, or combinations thereof. Clause 9 3. The composition of claim 2, wherein the polymer matrix or resin is selected from polyurethane, epoxy, thermoset polymer, thermoplastic polymer, rubber, bismaleimide, polyimide, polyaryletherketone, or combinations thereof. Clause 10 10. The composition of claim 9, wherein the polymer matrix or resin is an epoxy. Clause 11 3. The composition of claim 2, which is a composite. Clause 12 12. The composition of claim 11, wherein the composite is disposed on the component, the composite having a thickness of from 0.01 μm to about 100 μm. Clause 13 12. The composition of claim 11, having a resistance of about 0.1 ohms / square to about 25 megaohms / square. Clause 14 13. The composition of claim 12, wherein the component is a vehicle component. Clause 15 15. The composition of claim 14, wherein the vehicle component is a rotor, a landing gear, an auxiliary power unit, an aircraft nose, a fuel tank, a tail cone, a panel, a coated lap joint between two or more panels, a wing-fuselage assembly, a structural aircraft composite, a fuselage-body joint, or a wing rib-skin joint. Clause 16 1. A method for producing a component, comprising contacting a metal-coated fiber material with an oxidizing agent and a monomer to form a first composition containing the metal-coated fiber material and a conductive polymer, and contacting the first composition with a polymer matrix or resin to form a second composition. Clause 17 17. The method of claim 16, wherein the oxidizing agent is an iron-containing oxidizing agent, a cerium-containing oxidizing agent, or a sodium-containing oxidizing agent. Clause 18 17. The method of claim 16, wherein the oxidizing agent is selected from iron paratoluenesulfonate, iron permanganate, iron sulfate, iron dichromate, cerium (IV) sulfate, sodium dichromate, ammonium persulfate, or a mixture thereof. Clause 19 19. The method of any one of clauses 16-18, further comprising heating the first composition to a temperature of about 40° C. to about 80° C. Clause 20 20. The method of claim 19, further comprising heating the second composition to a temperature of about 40° C. to about 80° C.

[0084] In general, the compositions and methods of the present disclosure provide compositions containing metal coated fibers and conductive polymers that, when incorporated into a polymer matrix or resin, can improve the electrical conductivity of the fibers and can provide significant weight savings, for example when the compositions of the present disclosure are composites placed on metal surfaces, such as vehicle components. The compositions (and composites) of the present disclosure also generally improve the strength and ductility of composite components, while maintaining or improving the electrical properties of the composite, for example, compared to conventional composites.

[0085] The description of various aspects of the present disclosure is presented for illustrative purposes only and is not intended to be exhaustive or limited to the disclosed embodiments. Many modifications and variations that do not depart from the scope and spirit of the disclosed aspects will be apparent to those skilled in the art. The terms used herein are selected to better explain the principles of the aspects, practical applications of the technology or technical improvements, or to allow the aspects disclosed herein to be understood by those skilled in the art. The foregoing is directed to aspects of the present disclosure, and other and further aspects of the present disclosure may be devised without departing from the basic scope.

Claims

1. A conductive polymer; a textile material having one or more metals disposed thereon; A composition comprising:

2. The composition of claim 1 further comprising a polymer matrix or resin.

3. 3. The composition of claim 2, comprising from about 50% to about 99% by weight of the polymer matrix or resin, based on the total weight of the composition.

4. 2. The composition of claim 1, wherein the conductive polymer is selected from polyaniline, poly(ethylenedioxythiophene), polypyrrole, or a mixture thereof.

5. 3. The composition of claim 2, comprising the conductive polymer and metal coated fibers at a loading of about 1% to about 20% by weight based on the total weight of the composition.

6. 6. The composition of claim 5, wherein the metal is selected from nickel, titanium, palladium, iron, cobalt, copper, aluminum, chromium, or mixtures thereof.

7. 7. The composition of claim 6, wherein the ratio of conductive polymer to metal coated fiber is from about 0.002:1 to about 4:

1.

8. 10. The composition of claim 1, wherein the fibers are selected from carbon, nylon, fiberglass, polyacrylonitrile, or combinations thereof.

9. 3. The composition of claim 2, wherein the polymer matrix or resin is selected from polyurethanes, epoxies, thermoset polymers, thermoplastic polymers, rubbers, bismaleimides, polyimides, polyaryletherketones, or combinations thereof.

10. The composition of claim 9 , wherein the polymer matrix or resin is an epoxy.

11. The composition of claim 2 which is a composite.

12. The composition of claim 11, wherein the composite is disposed on the component, the composite having a thickness of from 0.01 μm to about 100 μm in thickness.

13. 12. The composition of claim 11 having a resistance of about 0.1 ohms / square to about 25 megaohms per square.

14. 13. The composition of claim 12, wherein the component is a vehicle component.

15. 15. The composition of claim 14, wherein the vehicle component is a rotor, a landing gear, an auxiliary power unit, an aircraft nose, a fuel tank, a tail cone, a panel, a coated lap joint between two or more panels, a wing-fuselage assembly, a structural aircraft composite, a fuselage-body joint, or a wing rib-skin joint.

16. contacting the metal-coated fiber material with an oxidizing agent and a monomer to form a first composition containing the metal-coated fiber material and a conductive polymer; and contacting the first composition with a polymer matrix or resin to form a second composition; A method for manufacturing a component, comprising:

17. 17. The method of claim 16, wherein the oxidizing agent is an iron-containing oxidizing agent, a cerium-containing oxidizing agent, or a sodium-containing oxidizing agent.

18. 17. The method of claim 16, wherein the oxidizing agent is selected from iron paratoluenesulfonate, iron permanganate, iron sulfate, iron dichromate, cerium (IV) sulfate, sodium dichromate, ammonium persulfate, or mixtures thereof.

19. 17. The method of claim 16, further comprising heating the first composition to a temperature of about 40°C to about 80°C.

20. 20. The method of claim 19, further comprising heating the second composition to a temperature of about 40°C to about 80°C.

Citation Information

Patent Citations

  • Carbon fiber and resin composition using the same, molding material and molded article

    JP2002155471A

  • Electricity conductive material

    JP2018052798A

  • Electrostatic dissipative compositions and methods thereof

    JP2018080320A

  • Composite polymeric material for EMI shielding

    US20070056769A1